The savvy investor's guide to building wealth through alternative investments - Baker, H. Kent; Nofsinger, John R.; Spieler, Andrew C. (Emerald Publishing Limited, 2021)
Do you want to see your wealth grow? If so, then this easy-to-read guide that focuses on alternative investments - hedge funds, private equity, real estate, commodities, and infrastructure - is just for you. The fourth book in The H. Kent Baker Investments Series attempts to remove some of the mystery surrounding these investments so that you can determine whether any of these are right for you. If you're willing to gain the necessary knowledge, you may be able to build long-term wealth by taking advantage of the benefits that each investment has to offer. The Savvy Investor's Guide to Building Wealth Through Alternative Investments is written for investors familiar with traditional investments but with limited knowledge of alternative assets and strategies.
Includes index.
Keywords: Investments.; Business & Economics, Investments & Securities -- General.; Investment & securities.; elektronické knihy; electronic books